Music interventions to reduce stress and anxiety in pregnancy: a systematic review and meta-analysis - Corbijn van Willenswaard, K; Lynn, F; McNeill, J; McQueen, K; Dennis, C; Lobel, M; Alderdice, F (BioMed Central, 2017)
Background Stress and anxiety are common in pregnancy and shown to have adverse effects on maternal and infant health outcomes. The aim of this review and meta-analysis was to assess the effectiveness of music-based interventions in reducing levels of stress or anxiety among pregnant women. Methods Six databases were searched using key terms relating to pregnancy, psychological stress, anxiety and music. Inclusion criteria were randomised controlled or quasi-experimental trials that assessed the effect of music during pregnancy and measured levels of psychological stress or anxiety as a primary or secondary outcome. Two authors independently assessed and extracted data. Quality assessment was performed using The Cochrane Collaboration risk of bias criteria. Meta-analyses were conducted to assess stress and anxiety reduction following a music-based intervention compared to a control group that received routine antenatal care. Results Five studies with 1261 women were included. Music interventions significantly reduced levels of maternal anxiety (Standardised Mean Difference (SMD): -0.21; 95% Confidence Interval (CI) -0.39, −0.03; p = 0.02). There was no significant effect on general stress (SMD: -0.08; 95% CI -0.25, 0.09; p = 0.35) or pregnancy-specific stress (SMD: -0.02; 95% CI -0.19, 0.15; p = 0.80). The methodological quality of included studies was moderate to weak, all studies having a high or unclear risk of bias in allocation concealment, blinding and selective outcome reporting. Conclusions There is evidence that music-based interventions may reduce anxiety in pregnancy; however, the methodological quality of the studies was moderate to weak. Additional research is warranted focusing on rigour of assessment, intensity of interventions delivered and methodological limitations.